Experimental investigation of the performance of a hybrid photovoltaic/thermal solar system using aluminium cooling plate with straight and helical channels. (15th November 2017) - Salem, M.R.; Ali, R.K.; Elshazly, K.M.
Highlights: Active cooling for PV system using straight and helical channels has been carried out. Thermal and electrical performance for both channels were introduced. Both systems show better thermal and electrical efficiencies compared with uncooled panel. The consumed pumping power is negligible compared with the increase in the electrical power of the cooled panels. Cooled plate with straight channels is preferred to avoid high blockage that leads to high pressure drop and leakage. Abstract: This paper presents a field study for the performance of photovoltaic thermal (PVT) system that use aluminium cooling plate with straight and helical channels during July 2016. Three systems each of 0.37 m 2 commercial poly-crystalline PV panels have been installed at the faculty of engineering at Shoubra, Benha University, Cairo, Egypt (30.1°N Latitude). Two of the systems are cooled using straight and helical channels with dimensions of 10 × 10 mm 2 and compared with the uncooled panel. The results showed that an increase in average electrical efficiency of 17.7% to 38.4% with relative to uncooled panels for flow rate range of 0.25 to 1 L/min. The corresponding average thermal efficiency increases from 31.6% to 47.2% for straight channels and 34.6% to 57.9% for helical configuration. While the corresponding average exergy efficiency increases from 11.1% to 12.9% for straight channels and 11.5% to 13.5% for helical arrangement. The associated water pumping power in both configurations does not exceed 3.3% of the converted electrical power while the increase in the obtained electrical power is of 30% with relative uncooled cell power.